ANALISIS PENDAPATAN USAHATANI JAGUNG BERDASARKAN KEPEMILIKAN LAHAN DI DESA SANGKUB III KECAMATAN SANGKUUB KABUPATEN BOLAANG MONGONDOW UTARA - Rifani, Rahman; Sondakh, Mex Frans Lodwyk; Rumagit, Grace Adonia Josephine (Sam Ratulangi University, 2022)
This study aims to analyze the income of corn farmers in Sangkub III Village based on land ownership. This research was carried out from November to January 2022. The data used in this study were primary data and secondary data. Primary data was obtained through direct interviews with 20 respondents (10 respondents from owner farmers and 10 respondents from rented farmers) using a questionnaire. Secondary data were obtained from the government of Sangkub III Village and other institutions related to this research. Sampling method using simple random sampling method or simple random technique. The variables measured were the respondent's characteristics, land tenure status, expenditure, income and revenue. The data analysis method used is farm income analysis. The results showed that, the average income of corn farming in Sangkub III Village, Sangkub District, North Bolaang Mongondow Regency in one planting season was obtained by the owner farmer of Rp. 3,756,551/ha, while the average income obtained by rented farmers is Rp. 3,674,520/ha.